2016
DOI: 10.1111/nhs.12277
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a concept map teaching approach on nursing students’ critical thinking skills

Abstract: Nurses confront complex problems and decisions that require critical thinking in order to identify patient needs and implement best practices. An active strategy for teaching students the skills to think critically is the concept map. This study explores the development of critical thinking among nursing students in a required pathophysiology and pharmacology course during the first year of a Bachelor of Science in Nursing in response to concept mapping as an interventional strategy, using the Health Education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 16 publications
4
30
0
4
Order By: Relevance
“…Researchers in the United States conducted an experimental study and findings showed that nursing students in the CM group performed much better in the health education system than students in the control group. 7 Results of a study in Brazil showed that CM is a valid strategy to evaluate the learning-teaching process and can be used for education, research and reflection in nursing. 8 Find-…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in the United States conducted an experimental study and findings showed that nursing students in the CM group performed much better in the health education system than students in the control group. 7 Results of a study in Brazil showed that CM is a valid strategy to evaluate the learning-teaching process and can be used for education, research and reflection in nursing. 8 Find-…”
Section: Introductionmentioning
confidence: 99%
“…Longe de ser um modismo, o desenvolvimento de habilidades e competências sempre foi objetivo da educação e precisa ser entendido como um processo de formação integral, que não se restringe à transmissão de conteúdos. Em busca de atender às complexidades do cotidiano, a qualidade do conhecimento e as competências envolvidas tornaram-se imprescindíveis ao exercício profissional qualificado em decisões que exigem o pensamento crítico, a fim de identificar as necessidades do paciente e implementar as melhores práticas 3,4 .…”
Section: Introductionunclassified
“…KADDOURA, M., O. VAN-DYKE et al (2016). "Impact of a concept map teaching approach on nursing students' critical thinking skills."…”
Section: Conclusõesmentioning
confidence: 99%
“…Quadro (n.º 13) -KADDOURA, M., O. VAN-DYKE et al (2016) segundo identificação do estudo, objetivo, metodologia, resultados e conclusões. ARRUE, M. AND S. CABALLERO (2015).…”
Section: Conclusõesunclassified
See 1 more Smart Citation